Exchange Rate and Prices: Firms' Behaviour in the Open Economy - Caterina Colombo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1987)
This paper is concerned with the behaviour of firms operating in international markets, i.e. exporting and/or facing import competition, with specific reference to the effects of exchange rate movements.
Keywords: 330